2023
DOI: 10.1177/17562864221147743
|View full text |Cite
|
Sign up to set email alerts
|

Early neurological deterioration in patients with acute ischemic stroke: a prospective multicenter cohort study

Abstract: Background: There is still no precise knowledge of the causes of progression in patients with acute ischemic stroke (AIS), and we are unable to predict patients at risk. Objective: To explore the frequency, predictive factors, and the prognosis of early neurological deterioration (END) in patients with AIS Methods: In this prospective multicenter observational study, we assessed patients with AIS admitted to 18 hospitals in Henan, China. We defined END as an increase of ⩾2 points in total National Institutes o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 57 publications
0
13
1
Order By: Relevance
“…The results of this study also showed that a history of diabetes mellitus, baseline NIHSS score, and degree of carotid artery stenosis were associated with the development of END in patients with AIS, and that diabetes mellitus and baseline NIHSS level were independent risk factors for the development of END, which is consistent with previous studies. [27,28] Previous studies have confirmed that CRP and cardiogenic embolism may be risk factors for the development of END, but no significant difference was seen in the present results (P > .05), considering the following aspects. First, after the occurrence of AIS, ischemic brain injury site releases a large number of inflammatory mediators and chemokines, induces the production of CRP, and increases the endothelial permeability of blood vessels and destroys the blood-brain barrier through direct and indirect pathways, aggravating the injury of ischemic brain tissues, and the high and low levels of its indexes respond to the degree of inflammatory response, which plays an important role in the occurrence of atherosclerosis and AIS and the progression of the disease.…”
Section: Discussioncontrasting
confidence: 73%
“…The results of this study also showed that a history of diabetes mellitus, baseline NIHSS score, and degree of carotid artery stenosis were associated with the development of END in patients with AIS, and that diabetes mellitus and baseline NIHSS level were independent risk factors for the development of END, which is consistent with previous studies. [27,28] Previous studies have confirmed that CRP and cardiogenic embolism may be risk factors for the development of END, but no significant difference was seen in the present results (P > .05), considering the following aspects. First, after the occurrence of AIS, ischemic brain injury site releases a large number of inflammatory mediators and chemokines, induces the production of CRP, and increases the endothelial permeability of blood vessels and destroys the blood-brain barrier through direct and indirect pathways, aggravating the injury of ischemic brain tissues, and the high and low levels of its indexes respond to the degree of inflammatory response, which plays an important role in the occurrence of atherosclerosis and AIS and the progression of the disease.…”
Section: Discussioncontrasting
confidence: 73%
“…Patients in this study were enrolled from a prospective, multi-center, web-based registry study (ChiCTR2100045258) from January 2021 to January 2022. 14 This registry study enrolled patients with acute ischemic stroke who were admitted to regional stroke centers. Throughout the entire study, information on patients demographics, treatments and prognosis is collected in a standardized manner, and the integrity of the data is monitored monthly by dedicated quality control staff.…”
Section: Study Populationmentioning
confidence: 99%
“…Studies report a higher prevalence of microalbuminuria in ischemic stroke patients (14%-60%) compared to healthy individuals [ 3 ]. Early neurological deterioration (END), a significant worsening of neurological function within hours or days of a stroke, severely impacts patient outcomes [ 4 , 5 ]. Predictors of END include large infarct size, severe intracranial artery stenosis, specific lesion locations, high low-density lipoprotein cholesterol, and diabetes mellitus [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%